Bivalirudin Versus Unfractionated Heparin in Patients With Cardiogenic Shock Requiring Venoarterial Extracorporeal Membrane Oxygenation. Issue 1 (11th April 2022) - Uricchio, Marissa N.; Ramanan, Raj; Esper, Stephen A.; Murray, Holt; Kaczorowski, David J.; D'Aloiso, Brandon; Gomez, Hernando; Sciortino, Christopher; Sanchez, Pablo G.; Sappington, Penny L.; Rivosecchi, Ryan M.
Abstract : This study evaluated differences in efficacy and safety outcomes with bivalirudin compared with unfractionated heparin (UFH) in patients with cardiogenic shock requiring venoarterial extracorporeal membrane oxygenation (VA ECMO). We performed a retrospective study at an academic medical center that included patients greater than 18 years of age supported with VA ECMO due to cardiogenic shock from January 2009 to February 2021. The primary endpoint was ECMO-associated thrombotic events normalized to duration of ECMO support. Secondary safety endpoints included major bleeding (per ELSO criteria) and blood product administration. Overall, 143 patients were included in our analysis with 54 having received bivalirudin and 89 having received UFH. Median duration of ECMO support was 92 (interquartile range, 56–172) hours. ECMO-associated thrombotic events per ECMO day were significantly less among those that received bivalirudin ( P < 0.001). In adjusted regression, bivalirudin was independently associated with an increased time to thrombosis when compared with UFH (Exp[B] –3.8; 95% confidence interval, 1.7–8.8; P = 0.002). Patients receiving bivalirudin experienced less major bleeding events ( P = 0.02) with less total red blood cell and fresh frozen plasma administration ( P = 0.04 and P = 0.03, respectively). Bivalirudin is a safe and efficacious alternative to UFH in patients requiring VA ECMO for cardiogenic shock.